Pengembangan Model Kegiatan Ekstrakurikuler Menjahit untuk Meningkatkan Soft Skill dan Kesiapan Berwirausaha Siswa MTs N 2 Purworejo - Vivi Kusumadewi; Supriadi, Didi (Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to develop a management model for sewing extracurricular activities based on Project-Based Entrepreneurial Learning (PjBEL) at MTs N 2 Purworejo, designed to enhance students’ soft skills and entrepreneurial readiness. The research employed a Research and Development (R&D) approach, adapting the Borg and Gall development model with a simplified seven-step procedure: preliminary data collection, planning, initial product development, initial testing, product revision, field testing, and final revision. The study involved subject matter experts, language experts, entrepreneurship experts, and 32 students participating in the sewing extracurricular program. Data were collected through observation, documentation, and questionnaires. The findings indicate that the developed extracurricular sewing module received “excellent” validation ratings from all expert reviewers and a highly positive response from students. Furthermore, observation results demonstrated a notable improvement in students’ soft skills, increasing from 63.95% to 70.8% following the implementation of the module. These results suggest that the PjBEL-based management model is effective in promoting soft skill development and entrepreneurial orientation at the madrasah level.